Influence of melatonin on the kidneys of rats with experimental diabetes mellitus type 2 - Semenko, A. V.; Murdasov, Y. V.; Kirichenko, S. V.; Zhyliuk, V. I.; UshakovаG. A. (Regulatory Mechanisms in Biosystems, 2020)
Diabetes mellitus is characterized by numerous pathological changes in the body. Under conditions of diabetes, hyperglycemic intoxication of the organism rapidly develops, which in turn leads to an increase of oxidative stress with subsequent disturbance of the anatomical and functional integrity of the components of organisms. Today, the search for the substances that would contribute to the multi-vectoral effect on the negative consequences of diabetes is actively being pursued. Melatonin is one of such substances. In this work, we studied the effect of melatonin on oxidative stress markers (oxidized products content, activities of superoxide dismutase and catalase), the concentration of metabolism end products (creatinine and urea), main ions concentration (potassium and chlorine), and protein content (total protein and electropherogram in polyacrylamide gel), enzymatic activity of gamma-glutamyltrasferase in the cytosolic fraction of rat kidneys under condition of type 2 diabetes mellitus (EDM2). Experimental studies were performed on 18 white adult Wistar rats divided into three groups (control, group with EDM2 and group with EDM2, which were treated with melatonin). The increase of concentration of oxidized products, the activity of catalase and gamma-glutamyltrasferase, creatinine, urea, K+ and Cl– and the decrease of concentration of superoxide dismutase in the rats’ kidneys was noted after development of EDM2. The electrophoretic proteinogram of the cytosolic proteins obtained from the rats’ kidneys showed an increase of content of high-molecular-weight and a decrease of low-molecular-weight proteins. Administration of melatonin in a dose of 10 mg/kg of body weight for 7 days after development of EDM2 restored the studied parameters almost to the control group values. Therefore, the influence of melatonin can prevent chronic development of oxidative stress in kidneys under hyperglycemic intoxication, and lead to normalization of kidney function and the restoration of homeostasis.